Financial management system - Ahmad Haziri, Mohamed Amin (2009)
Many university students have problem with planning their spending.Most of the student got financial support by loan from Perbadanan Tabung Pendidikan Tinggi Nasional (PTPTN) and the loan was given for 1 semester duration.Some of the students already finish the loan before the semester ends and this create a problem as they might not have other source of income to support for the end of semester.Some student started to do small business and some will take loan from friends and family.They did not plan for the loan they get and finish them without them noticing it.The system will divide the money to separate portions to guide the users how much they can use the money and also have saving for future. This system will keep all the student transaction in and out from the pocket.The system can be access through internet from any computer which has internet connection.There are also wap support for small device such as hand phone to ease of inserting the transaction as it occur and commit. The system is updated real time,so student can always watch their financial state.This system developed by adding human heuristics principles in mind so that user can easily familiar with the system as they start using it.This can also reduce user frustration in using new system.